The Implied Meaning of Thanking Expressions in Students’ Drama Performance: “The Pursuit of Happyness “Drama - Eripuddin Eripuddin; Jufrizal Jufrizal; Agustina Agustina (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study investigated thanking expressions used in a drama performance at the English Department of Pasir Pengaraian. Thanking expression has an essential role in giving a sense of communication. The research design was descriptive qualitative, especially in phenomenology. The data was collected from 29 sixth-semester students. The data were collected by using non-participant observation. This research data was analyzed by using Hymes' theory (1972) and Yule (1996). Based on the research, there were 60 thanking expressions used in this drama. The result of data showed some implied meanings of thanking expressions in this drama. There were 14 data (27%) as acknowledging a major favor, 8 data (15%) as acknowledging a favor, 4 data (7%) as assuring a person of one's gratitude, 3 data (6%) as dismissing a person's service, 15 data (29%) as closing the conversation, 6 data (10%) as accepting an offer, 1 data (2 %) as making the hearer feel good (phatic function), and 1 data (2 %) as ending the conversation. Thus, the implied meaning of thanking expression would be a particular function to fill gab language and culture in teaching and learning, especially in drama performance